Implementing the MOVE! Weight-Management Program in the Veterans Health Administration, 2007-2010: A Qualitative Study - Weiner, Bryan J. (Centers for Disease Control and Prevention, 2011)
INTRODUCTION: One-third of US veterans receiving care at Veterans Health Administration (VHA) medical facilities are obese and, therefore, at higher risk for developing multiple chronic diseases. To address this problem, the VHA designed and nationally disseminated an evidence-based weight-management program (MOVE!). The objective of this study was to examine the organizational factors that aided or inhibited the implementation of MOVE! in 10 VHA medical facilities. METHODS: Using a multiple, holistic case study design, we conducted 68 interviews with medical center program coordinators, physicians formally appointed as program champions, managers directly responsible for overseeing the program, clinicians from the program's multidisciplinary team, and primary care physicians identified by program coordinators as local opinion leaders. Qualitative data analysis involved coding, memorandum writing, and construction of data displays. RESULTS: Organizational readiness for change and having an innovation champion were most consistently the 2 factors associated with MOVE! implementation. Other organizational factors, such as management support and resource availability, were barriers to implementation or exerted mixed effects on implementation. Barriers did not prevent facilities from implementing MOVE! However, they were obstacles that had to be overcome, worked around, or accepted as limits on the program's scope or scale. CONCLUSION: Policy-directed implementation of clinical weight-management programs in health care facilities is challenging, especially when no new resources are available. Instituting powerful, mutually reinforcing organizational policies and practices may be necessary for consistent, high-quality implementation.